In search of a reliable electrophysiological marker of oculomotor inhibition of return. (27th June 2014) - Satel, Jason; Hilchey, Matthew D.; Wang, Zhiguo; Reiss, Caroline S.; Klein, Raymond M.
Abstract Inhibition of return (IOR) operationalizes a behavioral phenomenon characterized by slower responding to cued, relative to uncued, targets. Two independent forms of IOR have been theorized: input‐based IOR occurs when the oculomotor system is quiescent, while output‐based IOR occurs when the oculomotor system is engaged. EEG studies forbidding eye movements have demonstrated that reductions of target‐elicited P1 components are correlated with IOR magnitude, but when eye movements occur, P1 effects bear no relationship to behavior. We expand on this work by adapting the cueing paradigm and recording event‐related potentials: IOR is caused by oculomotor responses to central arrows or peripheral onsets and measured by key presses to peripheral targets. Behavioral IOR is observed in both conditions, but P1 reductions are absent in the central arrow condition. By contrast, arrow and peripheral cues enhance Nd, especially over contralateral electrode sites.